Karakterisasi Kualitas Briket Biomassa Campuran Tempurung Kelapa Dengan Buah Ketapang Terhadap Nilai Kalor dan Laju Pembakaran - Kurniawan, Muhammad Dafa; Sriwardhani, Nyenyep (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2000)
This study aims to determine the characterization of biomass briquettes made from a mixture of coconut shell powder and ketapang fruit powder, using three different composition ratios. The indicators analyzed are the calorific value and the combustion rate produced by the biomass briquettes. The research method used is the Taguchi Method with an experimental model. Three composition ratios of ketapang fruit charcoal powder to coconut shell charcoal powder were used: 60/40, 50/50, and 40/60. All briquette samples were produced with the same density and the same amount of tapioca starch binder, with a density of 0.01083 g/cm³ and 7% tapioca starch based on the total briquette mass of 150 grams. The density measurement in this study follows ASTM D2395-17 standards, with the volume of the biomass briquette calculated as 3.14 × (1.95 cm)² × 3.94 cm. The results show that the composition ratio of 40/60 (ketapang fruit powder/coconut shell powder) produced the highest performance in terms of calorific value and combustion rate, with a calorific value of 6085.38 kcal/g and a combustion rate of 0.20396 g/min